The canary code a guide to neurodiversity, dignity, and intersectional belonging at work - Praslova, Ludmila N. (Ascent Audio, 2024)
From a member of the Thinkers50 2024 Radar cohort of global management thinkers most likely to impact workplaces and the first person to have written for Harvard Business Review from an autistic perspective comes The Canary Code-a guide to win-win workplaces. Currently, despite their skills and work ethics, members of ADHD, autism, Tourette Syndrome, learning differences, and related communities face drastic barriers to hiring and advancement. In the US, 30-40% of neurodivergent people and 85% of autistic college graduates struggle with unemployment. Lack of flexibility, transparency, and psychological safety excludes neurodivergent, disabled, and multiply marginalized talent-and leaves most employees stressed and disengaged. This unique book is a guide to change-making for CEOs, managers, HR leaders, and everyone who wants to contribute to building a more inclusive world. The Canary Code combines lived experience with academic rigor, innovative thought leadership, and lively, accessible writing. To support different types of listeners, academic, applied, and lived experience content is clearly identified, helping listeners choose their own adventure.